THE STUDY ABOUT ELECTRIC VEHICLES IN LITHUANIA - Ginavičienė, Jurgita; Sprogytė, Indrė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Electric cars are very important for the circular economy. If we are using the electric vehicle we can reduce emission savings and protect the environment. Electric vehicles can contribute to energy efficiency, reducing carbon emissions unfortunately, despite everything, the development of the electric vehicle market in Lithuania remains relatively slow. Electric vehicles are more expensive than traditional vehicles, there is a lack of the necessary infrastructure, and consumers do not have enough information on the benefits of green cars. The main purpose of this article is to research electric vehicles market in Lithuania. The methods of research include scientific literature analysis, statistics data comparative analysis. Electrical vehicle market in Lithuania is growing. From 2017 until 2020 M1 class electric cars was purchased 35 %. At the same period the market of new electric car increased 50 %, used electric vehicle increased only 27 %.